Resin Infiltration of Caries in Primary Molars in a Community Setting: 24-Month Randomized Controlled Trial Findings. (July 2017) - Foster Page, L.A.; Beckett, D.; Ahmadi, R.; Schwass, D.R.; Leon de la Barra, S.; Moffat, S.M.; Meldrum, A.; Thomson, W.M.
This study aimed to assess whether resin infiltration of primary molar proximal lesions is more effective than noninvasive measures in radiographically controlling carious lesion progression into the dentin. A split-mouth randomized controlled trial included 90 children, each with 2 proximal lesions confined to the inner half of the enamel or ≤0.5 mm into the dentin. For each child, lesions were randomly allocated to test (infiltration: DMG Icon preproduct and fluoride varnish) or control (fluoride varnish) status. The primary outcome measure was 24-mo radiographic lesion progression. Placement of a restoration during the study period was counted as lesion progression. Proportions of teeth with progressed lesions were compared using the McNemar test. Children also reported on the treatment's acceptability to them. Children (46% female) ranged in age from 6 to 9 y. Their mean number of decayed, missing, and filled teeth (d3 mft) was 2.8 (SD 2.6). At baseline, 58% and 42% of children were at moderate and low risk, respectively. Test and control lesions presented with similar radiographic lesions at baseline. At the 24-mo follow-up, 6 children had moved and 30 teeth had exfoliated. In the test and control groups, 15 of 66 lesions (22.7%) and 30 of 69 lesions (43.5%) had progressed, respectively (P < 0.05). The 2-y therapeutic effect (based on pairwise radiographic readings) of infiltration over fluoride varnish was 20.8% (95% confidence interval, 10.6%−30.2%). Nearly all children (96.7%) had enjoyed their visit to the clinic, and more than two-thirds (72.2%) were not worried about returning for treatment. Infiltration is more efficacious than fluoride varnish for controlling carious lesion progression in proximal lesions in primary molars, and most children find the treatment acceptable (Australian New Zealand Clinical Trials Registry ANZCTR.org.au ACTRN12611000827932). Knowledge Transfer Statement : These study findings can help clinicians decide which caries management approach they wish to use to prevent progression of proximal lesions in primary molars. With consideration of cost and patient preference, this information could lead to more appropriate therapeutic decisions.